Study fenologi pembungaan Santalum album Linn di Wanagama I, Yogyakarta=Phenology Study of Flowering of Santalum album Linn in Wanagama I, Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Santalum album (sandalwood) is one of the fancy woods species, and the species at present has been classified as an endangered species. One of the efforts to increase the number of this species was by studying the flowering phenology. The information was very important for the forest development planner, particularly in choosing the best strategy to provide sufficient high quality seed. The objective of the study was carried out in sandalwood plantation, located in block 17, Wanagama Forest Research I, Yogyakarta. The duration of the study was 5 month, started from. June to October 2004. To Obtain information on flowering and fruiting phenology, analyzed. To complete one flowering period, from flower initiation to fruit and seed maturation, sandalwood needs 107 days. The initiation was started one June and maturation of fruit would be on September. The peak of flowering season was in July, with 18,15 % of trees with flowers. An thesis occurs at about 8 to 9 in the morning, or 3 to 5 in the afternoon. Sandalwood flowers was categorized in protandri dichogamy flowers type. The male reproduction organ was receptive before the anthesis, while the stigma was receptive in 12 - 24 hours after anthesis.